(untitled) (Journal of Human Sciences, 2022)
This Almighty said : ( Among the believers are men true to what they promised Allah. Among them is he who has fulfilled his vow [to the death], and among them is he who awaits [his chance And they did not alter the terms of their commitment by any alteration) (Al-Ahzāb 23) This research aims to shed light on the history of the honourable and bright jihad movement that our ancestors wrote with their blood and their pure selves through the biography of the AlmujahidSaleh Al-Atyush, the leader of the homes of the Maghribi tribe in Ajdabiya, and we will discuss his participation and leadership of the battles in the region extending from Ajdabiya to Sirte, the most important of which was the famous battle of Al-Qardabiya in which he participated In April 1915 AD, he was at the head of the Mujahideen forces coming from east of Sirte, the Battle of BirAbilal, the Battle of Al-Kahrab and the Battle of Al-Buraiqah on June 10, 1923 AD. Jihad movement under the leadership of Idris Al-Senussi. In this research, we also present his rejection of all attempts at truce and reconciliation or surrender to the Italian forces, and his enemies witnessed this. General (Rodolfo Gratisani) said about him: “All attempts were made to get him to submit to the government by declaring his surrender, but in vain in front of his unrelenting mentality and his arrogance as A arrogant and arrogant leader.